Three Naturally-Occurring Psychedelics and Their Significance in the Treatment of Mental Health Disorders - Vorobyeva, Nataliya; Kozlova, Alena A. (Frontiers in Pharmacology, 2022)
Classical psychedelics represent a family of psychoactive substances with structural similarities to serotonin and affinity for serotonin receptors. A growing number of studies have found that psychedelics can be effective in treating various psychiatric conditions, including post-traumatic stress disorder, major depressive disorder, anxiety, and substance use disorders. Mental health disorders are extremely prevalent in the general population constituting a major problem for the public health. There are a wide variety of interventions for mental health disorders, including pharmacological therapies and psychotherapies, however, treatment resistance still remains a particular challenge in this field, and relapse rates are also quite high. In recent years, psychedelics have become one of the promising new tools for the treatment of mental health disorders. In this review, we will discuss the three classic serotonergic naturally occurring psychedelics, psilocybin, ibogaine, and N, N-dimethyltryptamine, focusing on their pharmacological properties and clinical potential. The purpose of this article is to provide a focused review of the most relevant research into the therapeutic potential of these substances and their possible integration as alternative or adjuvant options to existing pharmacological and psychological therapies.